Using a Studio-Academic Partnership to Advance Public Health Within a Pragmatic Yoga Setting. (September 2019) - Harden, Samantha M.; Steketee, Abby M.; Kelliher, Rachel; Mason, Keala A.; Fitzwater Boyle, Nicole
Objectives: To explore community-based yoga studio practitioners' psychosocial variables, behaviors, and studio satisfaction.Methods: Concurrent mixed-methods study consisted of a survey for demographic variables and psychosocial variables of interest (e.g., mindfulness, self-compassion, physical activity participation) and interviews regarding reasons for participating at the yoga studio.Results: Participants (N = 138) were, on average, 35.58 ± 14.09 years old and predominantly female (91.3%), married (40.6%) or single (37%), Caucasian (75%), and college (25.4%) or graduate/medical school (45%) educated, with 54% meeting physical activity recommendations. On a 5-point Likert-type scale, participants reported being moderately cohesive ( M sumscore = 3.87 ± 0.62), stressed ( M sumscore = 3.2 ± 0.39), mindful ( M sumscore = 3.4 ± 0.41), and self-compassionate ( M sumscore = 3.26 ± 0.56). A rapid content analysis of interviews (n = 18), indicated that participants primarily practiced at the studio for the sense of community.Conclusions: Yoga practitioners reported positive perceptions and behaviors; however, opportunities remain for interventions to improve mental and physical health among individuals already attending a yoga studio. Through an academic-studio partnership, studio offerings may include low-dose evidence-based interventions to improve access to and uptake of a yoga practice.